How final year chemical engineering students cope with learning in English - Mohd. Omar, Noor Abidah; Ibrahim, Ruzaini (2010)
There seems to be little information found in reports regarding the final year chemical engineering students’ situation of learning in English. Since the students’ learning condition in English is unknown, this issue has captured the interest of the researcher and there is a need for further investigation on the topic. The focus of the research is on the existence of problems faced by final year chemical engineering students when learning in English and strategies of overcoming them. A total of 90 final year chemical engineering students and two lecturers from the Faculty of Chemical Engineering and Natural Resources Engineering were involved in the study. The data needed for the research were collected via questionnaires and interview sessions. The questionnaires used contained 38 questions and the interview sessions consisted of ten questions. The data gathered were analyzed using descriptive statistics where percentages were used to show the results of the research. The overall findings indicate that the final year chemical engineering students were able to cope well with learning in English.